Alih Fungsi Lahan Pertanian dan Kesejahteraan Masyarakat di KEK Mandalika : Studi Kasus Desa Kuta - Nadia Putri; Diswandi Diswandi; Baiq Saripta Wijimulawiani (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to identify the background of the community surrounding the Mandalika Special Economic Zone (KEK) in converting agricultural land and analyze the implications of this land use change on community welfare. The research approach used a quantitative method with a case study design. Data were collected through field observations, in-depth interviews with the community and related parties, and documentation from various relevant sources. Data analysis was carried out through the stages of data reduction, data presentation, and verification to obtain accurate conclusions. The results show that agricultural land conversion by the community is influenced by various factors, including economic considerations, government policy encouragement related to tourism development, and the community's need to increase income and standard of living. Furthermore, the results revealed that land use change has a dual impact on community welfare. On the one hand, there is economic improvement through easier access to jobs and new business opportunities in the non-agricultural sector. However, on the other hand, social and cultural changes arise due to shifts in livelihoods, as well as threats to local food security. Overall, land use change in the Mandalika SEZ contributes to improving economic welfare, but poses challenges in terms of social and environmental sustainability.